Islamic work ethics as a key engine of endogenous economic growth - Asma Raies (Islamic Economic Studies (IES), 2022)
Purpose God promised pious individuals who obey to His commandments, to increase their economic well-being. Although it is difficult to demonstrate with figures in hand this causality relationship, Muslims must believe in its existence and robustness at both the individual and collective levels, as it is argued in Qur'an and the Prophetic Narration. We aim in this paper to model this positive relationship between Islamic work ethics and economic growth and prove theoretically its existence. Design/methodology/approach We develop an endogenous growth model very close technically to Lucas-Uzawa model (1988) in which the human capital defined as the individual's skill level acquired through formal education and learning by doing is replaced by ethical capital (piety). Findings The model proves theoretically that Islamic ethics are a key engine of endogenous economic growth and that the underdevelopment of Muslim populations is due to their low ethical capital (lack of piety). Practical implications The study recommends some policies such as providing formal religious education at all educational levels (elementary, secondary and higher levels) and promoting ethical values such as piety, sincerity, transparency, etc., through media and cultural institutions. Also, managers could provide courses and training to their workers to teach them Islamic work ethics. Originality/value This paper is the first to mathematically model Islamic work ethics as endogenous phenomena in socioeconomic systems and study theoretically their contributions to economic growth.
Keywords: I2; J2; J3; H2; H5; 330; Islamic work ethics; Piety; Ethical capital; Human capital; Endogenous growth